Inorganic chemistry: Solutions Manual Accompany - Hagerman, Michael; Schnabel, Chris ([S.l.] : W. H. Freeman, 2006)
The Solutions Manual contains complete solutions to the Self-tests and end-of-chapter exercises .
Authors - Shriver & Atkins